2011
DOI: 10.1007/s11630-011-0445-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on film cooling performance of pressure side in annular cascades

Abstract: Experimental investigations were conducted to study the film cooling performance in a low speed annular cascades using Thermochromic Liquid Crystal (TLC) technique. The test blade was placed in the second stage, where 18 blades were installed with chord length of 124.3 mm and height of 99 mm. A film hole with diameter of 4 mm, angled 28° to the tangential of the pressure surface in streamwise, was set in the middle span of the blade.The Reynolds number based on the outlet mainstream velocity and the blade chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Acharya [3] made a comprehensive review on lots of numerical works of film cooling during recent twenty years. No matter experimental or numerical works, most of them are concerned about the effects of various aerodynamic and geometrical parameters, such as blowing ratio, inclination angle, the shape of film cooling hole and compound angle on cooling performance [4][5][6][7][8]. However, there seems few studies on the influencing mechanism of these parameters and the evolutionary mechanism of coherent structure, which are pivotal and theoretical problems for film-cooling investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Acharya [3] made a comprehensive review on lots of numerical works of film cooling during recent twenty years. No matter experimental or numerical works, most of them are concerned about the effects of various aerodynamic and geometrical parameters, such as blowing ratio, inclination angle, the shape of film cooling hole and compound angle on cooling performance [4][5][6][7][8]. However, there seems few studies on the influencing mechanism of these parameters and the evolutionary mechanism of coherent structure, which are pivotal and theoretical problems for film-cooling investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Eckert (1970), has studied experimentally, the effect of the blowing ratio for the gas-to-gas film cooling in a cylindrical hole with air as a coolant fluid; this is one of the early works done in film cooling. In most studies, the film cooling effectiveness for small blowing ratios has been studied and it has been shown that by increasing the blowing ratio, the film cooling effectiveness increases (Li and Deng, 2011; Tao et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both the heat transfer coefficient and cooling effectiveness increase with Reynolds number. Li et al [7] investigated the film cooling characteristics in annular turbine cascades using thermochromic liquid crystal (TLC). Results showed that the film coverage and cooling effectiveness increase with the rising of mainstream Reynolds number.…”
Section: Introductionmentioning
confidence: 99%